Cover Image, Volume 75, Issue 3. Issue 3 (9th March 2018) - Doolin, Mary T.; Stroka, Kimberly M.
Abstract : ON THE BACK COVER: The cover image, by Mary T. Doolin and Kimberly M. Stroka, is based on the Research Article Physical confinement alters cytoskeletal contributions towards human mesenchymal stem cell migration, DOI: 10.1002/cm.21433 .